99.3k views
1 vote
??????????????????????????????

??????????????????????????????-example-1

1 Answer

1 vote

Answer:

x = - 7

Explanation:

Given the 2 equations

y - x = 9 → (1)

10 + 2x = - 2y → (2)

Rearrange (1) expressing x in terms of y by adding x to both sides

y = x + 9

Substitute y = x + 9 into (2)

10 + 2x = - 2(x + 9) ← distribute

10 + 2x = - 2x - 18 ( add 2x to both sides )

10 + 4x = - 18 ( subtract 10 from both sides )

4x = - 28 ( divide both sides by 4 )

x = - 7

User Nevir
by
5.0k points